Analysis of Tie Strength and Purchase Decision Involvement towards Word-of-Mouth Influence in Service Business - Qonitah , Ummu; Nuraeni, Shimaditya (KnE Social Sciences, 2020)
The increase in services must be handled, the high cost of services has the potential to shake off economic growth, according to an economic theory called Baumol’s disease. Therefore, services have to become more efficient and productive. A handling service business that mostly intangible are dissimilar from the product-based business. In service word of mouth (WOM) is important. This research would investigate the interaction and direct effects of tie strength which is an interpersonal force between sender and receiver of WOM and the receiver’s service purchase decision involvement which is an intrapersonal force on WOM influence. A secondary aim is to investigate how a distinctive conceptualization of perceived risk affects service purchase decision involvement. A conceptual model incorporating these constructs and associated hypotheses is developed and tested. This research is quantitative research conducted to explore the objective of the study. The researcher conducts a questionnaire to collect data. The purposeful sampling conducted on this research. PLS-SEM Analysis is used in this research for the data analysis. The result indicates tie strength and involvement positively affected WOM influence. However, the moderation effect whereby, tie strength was found to diminish the effect of involvement on WOM influence. The other finding is perceived risk has a highly significant effect on involvement. Also, the relationship between WOM influence and the purchase decision is positively significant. Keywords: Service, WOM Influence, Purchase Decision, Perceived Risk, Involvement, Tie Strength